The Transformation of Pigment in Fruit Wine, Precise Control of Pigment Formation, and Their Effect on Product Quality - Xiang Tan; Mengfan Ding; Chen Wang; Linhua Huang; Junying Bai (Foods)
Global fruit production is excessive, and fruit wine is a significant outcome of fruit processing. The pigment in fruit wine gives it a vibrant color and affects its quality, taste, and marketing. The pigments in fruit wines are commonly divided into three categories: anthocyanins, carotenoids, and chlorophylls. They are naturally synthesized pigments in plants that undergo complex biochemical changes that eventually tend to be stable in mature fruit wine, showing the color properties desired by consumers. Under normal circumstances, pigment molecules are unstable and have isomers, which makes it difficult to accurately identify and control them. In addition, biochemical changes produce a series of chemical derivatives that affect bioavailability and biological functions. This review summarizes the chemical basis, formation process, influencing factors, identification techniques, bioavailability, and bioactivity of fruit wine pigments, providing an important reference for the utilization of fruit resources and the development of high-quality fruit wine products.